The impact of the COVID-19 outbreak on supportive care for oral mucositis: current concepts and practice - Bonomo, Pierluigi (Support Care Cancer, 2021)
The outbreak of coronavirus disease 2019 (COVID-19) markedly affected the way healthcare professionals approach patients with cancer worldwide, not only in terms of therapeutic decision-making but also in terms of supportive care. With the rapid appearance of signs and symptoms and the need of close re-assessment, standard management of oral mucositis has been challenged by physical distancing and limited resources due to the global crisis. Building on the clinical experience developed during the acute phase by members of the Mucositis Study Group of the Multinational Association of Supportive Care in Cancer/International Society of Oral Oncology (MASCC/ISOO), the implications of COVID-19 on the prevention, assessment, and treatment of mucositis are critically reported. Inspired by the restructuring of supportive care measures in response to the pandemic, suggestions for new models of approaching acute side effects are also discussed.